Determining of trend variation in quality parameters of Shabestar plain underground water - Mehdi Panahi; Farhad Misaqi; Farid Ghanbari (علوم محیطی)
Introduction: Groundwater has long been the most ´trusted water source of human beings that is used in the agricultural and drinking sectors. In order to be aware of water condition and its optimized management, it is necessary to carefully examine groundwater level fluctuations and groundwater quality that are influenced by different factors. While carefully monitoring the fluctuations and quality of groundwater, we can have reliable planning in water supply and source management. Therefore, this study aims to determine the trend of changes in quality parameters of groundwater of Shabestar plain in order to understand the quality of groundwater and to specify its application. Material and methods: In this study, in order to understand the quality of Shabestar plain’s groundwater and to specify its application, the chemical results of 15 qualitative variables of groundwater samples belonging to 13 stations located in the study area during the years 1382-1999 were compared while using non-parametric Mann-Kendall test, and then effect of the first-order autocorrelation was eliminated from the data series. Slope of the trend line was calculated by the age method. The qualitative parameters in this study are total anions, total cations, EC, SAR, CL--, , Ca2+, TH, Ph, TDS,  , Na%, Na+, Mg2+ and K+ that are measured two times every year. Results and discussion: The results show that time series related to qualitative variables has ascending trend in most of stations (except Ali-shah station, Sefid-kamar station and low water months of Shabestar plain). They show positively significant trend at 5% level with 36 series (18%) in months of high level of water and with 17 series (9%) in months of low level of water.  Furthermore, “Ali-shah” and “Sefid-kamar” stations have the highest rank in the highest negative trend in two months with high- and low- levels of water. The comparison of stations suggests that quality of Shabestar plain’s groundwater has critical condition in southern part of plain. Generally we can conclude that the quality of groundwater in the study area has decreased over time. The results achieved from investigating the values of time series correlation coefficients of qualitative variables with normal annual precipitation in the periods (1382-1388) show that none of the qualitative variables have a special significance at the 5% level with the amount of annual precipitation. The overall result of this section suggests the lack of relationship between annual precipitation and qualitative variables, while ground water level has almost steadily dropped with quality variables during common statistical years (1383-1391).  Also, climatic variables such as rainfall, temperature and evaporation were not identified as factors in changing the qualitative characteristics of Shabestar plain’s groundwater and we come to this conclusion that their adverse changes were influenced by human factors. Conclusions: According to achieved results, we can say that if the current condition continues, it is not possible to steadily use groundwater source in Shabestar plain. Water quality will be negatively affected by the lack of treatment of urban and industrial wastewater, the release of agricultural wastes at the plains, adjacency to Urmia Lake, and the development of salt marsh.